Comparative Analysis of Classroom Management Instruments and Student Learning Motivation Using the Likert Scale - Helmiyatun Helmiyatun; Ahmad Ahmad (Progressive of Cognitive and Ability, 2026)
Purpose – Classroom management and learning motivation are essential components that influence students’ engagement and academic success. Although these constructs are closely interconnected, limited studies have comparatively examined students’ perceptions of both aspects within the same educational setting. This study aimed to analyze and compare students’ perceptions of classroom management and learning motivation in three senior secondary schools in Tempos Village, West Lombok. Methodology – This study employed a quantitative descriptive comparative design. A total of 227 students from MA Fathul Akbar NW Tempos, MA Nurul Huda Tempos, and SMK Hizbunnajah NW Tempos participated in the study. Data were collected using two Likert-scale questionnaires measuring classroom management and learning motivation. Descriptive statistics were used to summarize the data, while the Shapiro–Wilk test examined data normality and Levene’s test assessed the homogeneity of variances. All statistical analyses were conducted using R Studio. Findings – The findings showed that students perceived both classroom management and learning motivation positively. The mean classroom management score was 25.59, whereas the mean learning motivation score was 26.59. Learning motivation demonstrated greater variability than classroom management, indicating more diverse student perceptions. The Shapiro–Wilk test revealed that both variables were not normally distributed (p < 0.05), while Levene’s test indicated homogeneous variances (p > 0.05). These findings suggest that effective classroom management should be complemented by strategies that foster students’ learning motivation, particularly in educational settings characterized by diverse socio-cultural backgrounds. Novelty – This study provides a comparative analysis of classroom management and learning motivation using the same measurement framework and statistical assumptions, offering empirical evidence of the relationship between classroom climate and students’ motivational perceptions. Significance – The findings provide practical insights for teachers, school administrators, and educational policymakers in designing learning environments that effectively integrate classroom management practices with strategies to enhance students’ motivation and engagement.